2014
DOI: 10.1007/jhep01(2014)045
|View full text |Cite
|
Sign up to set email alerts
|

Vector condensate and AdS soliton instability induced by a magnetic field

Abstract: We continue to study the holographic p-wave superconductor model in the Einstein-Maxwell-complex vector field theory with a non-minimal coupling between the complex vector field and the Maxwell field. In this paper we work in the AdS soliton background which describes a conformal field theory in the confined phase and focus on the probe approximation. We find that an applied magnetic field can lead to the condensate of the vector field and the AdS soliton instability. As a result, a vortex lattice structure fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 78 publications
4
29
0
Order By: Relevance
“…(39) and (40). Thus, in this sense, the complex vector field model is still a generalization of the SU (2) Yang-Mills model in the holographic superconductors with hyperscaling violation, which supports the argument given in [54].…”
Section: Condensation and Phase Transitionsupporting
confidence: 77%
See 1 more Smart Citation
“…(39) and (40). Thus, in this sense, the complex vector field model is still a generalization of the SU (2) Yang-Mills model in the holographic superconductors with hyperscaling violation, which supports the argument given in [54].…”
Section: Condensation and Phase Transitionsupporting
confidence: 77%
“…Considering a fivedimensional AdS soliton background coupled to a Maxwell complex vector field, in Ref. [54] the authors reconstructed the holographic p-wave insulator/superconductor phase transition model in the probe limit and showed that the EinsteinMaxwell complex vector field model is a generalization of the SU (2) model with a general mass and gyromagnetic ratio. Other generalized investigations based on this new p-wave model can be found, for example, in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[2], a new holographic p-wave superconductor model was built by coupling a Maxwell-complex vector (MCV) field with the four-dimensional (4D) Schwarzschild AdS black hole [43], for related works, see Refs. [44][45][46][47][48][49][50]. It was shown that only the external magnetic field can induce the condensate, which is similar to result of the QCD vacuum phase transition in Ref.…”
Section: Introductionsupporting
confidence: 58%
“…Interestingly, the results showed that due to the nonminimal coupling between the vector field and the Maxwell field, the increasing magnetic field can induce superconductor phase transition even without charge density, which is similar to the QCD vacuum instability triggered by the strong magnetic field to develop the ρ-meson condensate [15]. Moreover, the investigation about the response of the external magnetic field on the p-wave phase transition also showed that the SU(2) YM model is a special case of the MCV model in five-dimensional (5D) soliton and 4D Lifshitz black holes [16][17][18]. Furthermore, considering the backreaction, the MCV model exhibits the rich phase structures, especially "retrograde condensation" [19][20][21].…”
Section: Introductionmentioning
confidence: 82%
“…where an important role in the presence of the external magnetic field [14,[16][17][18]. However, we will consider the case without the magnetic field in this paper; hence, it will not contribute to our work.…”
Section: Introductionmentioning
confidence: 99%